The Effectiveness of Using The Power of Two Learning Model on Mathematics Learning Outcomes in Tritech Informatics Vocational High School Students Medan T.P 2021/2022 - Wulandari, Putri; 'Afifah, Nur (Lembaga Riset Mutiara Akbar, 2022)
This study aims to determine whether the use of The Power of Two learning model is effective on mathematics learning outcomes. Students are given a test to get the results of learning mathematics, students' responses and activities towards learning. then the researcher describes the results in data analysis. The method used in this study is an experimental method using One Group Pretest Posttest Design. This research was conducted at Tritech Informatics Vocational School in class X-2 Software Engineering. The results of hypothesis testing conducted in this study indicate that the t-count value is 10.293 with the t-table value at a significant level = 0.05, which is 1.734, meaning that the t-count value > t-table value or 10.293 > 1.734. The gain test results obtained a gain index value of 0.73, interpreted into g > 0.7, said to be in the high category and at the level of effective effectiveness. Then it was concluded that The Power of Two model was effective on the mathematics learning outcomes of the students of SMK Tritech Informatika Medan